Pengaruh Search Rewrite and Test (SRT) terhadap Kemampuan Membaca Pemahaman Siswa Kelas VII SMPN 8 Padang - Kalsum, Yowanda; R., Syahrul; Ratna, Ellya (Universitas Negeri Padang, 2013)
This article was written to determine the effect of SRT on the reading comprehension class VII SMPN 8 Padang. Research data is the result of the final reading comprehension test given to both groups of samples. Data were collected by way of giving a test reading comprehension with SRT in the experimental group and the test reading comprehension without SRT in the control group. Reading comprehension ability of both groups were compared to see the effect of SRT by using t-test formula. The results showed that (1) the reading comprehension class VII SMPN 8 Padang using SRT are in good qualification; (2) the reading comprehension class VII SMPN 8 Padang without using SRT is more than enough to qualify; and (3) based on the results of the t-test concluded that there was a significant influence on the use of SRT in teaching reading comprehension class VII SMPN 8 Padang.